Answering Research Questions Using Survey Data: An Example from Maryland Agritourism - Bhandari, Prem (Dhaulagiri Journal of Sociology and Anthropology, 2024)
This brief paper discusses the concept, the sources, and the types of research questions that can be answered with survey data. In addition, I provided an example of answering a specific question using survey data with step-wise results from univariate (descriptive statistics), bivariate, and multivariate (e.g., binary logistic regression) analysis. I believe this paper will be useful to the young scholars.